Dependence of Latin America external sector on commodity prices: a contemporaneity analysis using a descriptive approach - Fioriti, Andrés (2019)
We seek to analyze the relationship between some macroeconomic variables and commodity prices in Latin America. The main hypothesis is that the economic performance in the area is tied to the pattern followed by the commodity prices. Moreover we expect to find that some commodities are more relevant than others. We find evidence supporting our former hypothesis but not the latter. An important result is that macroeconomic variables and commodity prices breaks followed a bimodal distribution over the last 60 years with one mode around the 70s and the other mode at the beginning of the 21th century.